Recipes for achieving customer loyalty: A qualitative comparative analysis of the dimensions of customer experience. (September 2020) - Pekovic, Sanja; Rolland, Sylvie
Abstract: Theoretical literature on customer experience (CX) agrees that the effects of customer experience on customer behavior depend on different combinations of its dimensions. In contrast with unidimensional or integrated approaches to CX, determining customer behavior requires specifying how the dimensions of CX interact. However, empirical research on the interactions between CX dimensions has not, to our minds, progressed sufficiently. Therefore, in this study, we have advanced CX research by empirically demonstrating the ways in which customer loyalty can result from various dimensions; we do this by focusing on synergies between different CX dimensions within a DIY sector. A sample of 603 consumers from France, applied to a fuzzy-set qualitative comparative analysis (fsQCA) model, reveals two configurations that firms can use to achieve superior customer loyalty. The findings also specify that complementarity and substitutability effects result among CX dimensions when they reflect a perfect match, and not simply by adding extra dimensions. Further analysis reveals both distinct features and similarities among generational cohorts, in terms of CX dimensions assessment, and their relevance for customer loyalty. This article thus contributes to existing research by tracing the multiple CX paths that can lead to enhanced performance for firms within the DIY sector.